PENINGKATAN KETERLIBATAN MAHASISWA DALAM KETERAMPILAN MENULIS BAHASA JERMAN MELALUI ASOSIOGRAM - Malia, Lia (LITERA, 2015)
<img src="data:image/png;base64,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